Exploring user interaction and satisfaction with virtual personal assistant usage through smart speakers - Jang, Yeibeech (Archives of Design Research, 2020)
Background Owing to the rapid penetration of smart speakers in South Korea, the virtual personal assistant (VPA) has become a more pervasive technology. The current study explored how users' psychological factors affect their evaluation of interaction experiences with VPAs. Specifically, this study investigated how VPA users' parasocial interaction, personification type, and loneliness influence their satisfaction with VPA use. Methods An online survey was conducted to examine the research questions. A total of 547 smart speaker users participated in the survey, and they were asked to answer a series of questions. A total of 534 responses were used for the statistical analysis. Results The results of the analysis showed that smart speaker users' parasocial interaction positively influenced satisfaction. Among the four different types of personification, only assistant/ helper type personification positively affected satisfaction. However, users' loneliness negatively influenced satisfaction. Conclusions Perceiving the VPA as a social being and personifying the device as if it were a human being increased users' satisfaction level, whereas loneliness decreased satisfaction. These findings suggest several practical implications for voice user interface design, and this study aims to broaden the scope of the discussion on human-machine communication as well.
Keywords: Loneliness; Parasocial Interaction; Personification Type; Satisfaction; Smart Speaker; Virtual Personal Assistant